Determination of Subgrade Reaction Modulus Considering the Relative Stiffnesses of Soil–Foundation Systems - Serdar Koltuk; Sadettin Topçu (Applied Sciences)
The interaction between raft foundations and soils is generally modeled with the help of linear elastic springs. The design of structural elements can only be computed when the modulus of subgrade reaction is accurately determined, which is a time-consuming process for raft foundations with relatively large sizes due to the input of many structural loads. In the present work, an approximate procedure is studied based on the relative stiffnesses of soil–foundation systems suggested by DIN—Technical Report 130. To estimate the behavior of soil–foundation systems (rigid or flexible), the limit values of relative stiffness are first determined for raft foundations on elastic soils with the stiffness moduli obtained from one-dimensional consolidation tests by using finite element analyses. Subsequently, the values of subgrade reaction moduli obtained from the FE analyses are compared and discussed with the subgrade reaction moduli determined by using the analytical method considering the relative stiffnesses of soil–foundation systems. It is shown that for a soil–foundation system with a relative stiffness ≥ 0.174, the subgrade reaction modulus obtained from the analytical method assuming a rigid system is about 1.5 to 2 times higher than that in the FE analyses. For a soil–foundation system with a relative stiffness ≤ 0.0004, the analytical method assuming a flexible system and the FE method yield a similar value of subgrade reaction modulus in the central area of the raft foundation.